PENGARUH MODEL RADEC TERHADAP HASIL BELAJAR RANAH KOGNITIF BAHASA INDONESIA SISWA KELAS V SDN 24 SINGKAWANG: Penelitian Kuantitatif - Ilma, Rafika Nurul; Setyowati, Rini; Mulyani, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims: 1) To find out the differences in learning outcomes of Indonesian language in the cognitive domain of acrostic material in the RADEC learning model compared to conventional methods in class V of SDN 24 Singkawang; 2) To find out how much influence the RADEC learning model has on learning outcomes of Indonesian language in the cognitive domain of acrostic material in class V of SDN 24 Singkawang. This research was conducted at SDN 24 Singkawang. This type of research is quantitative research with a quasi-experimental research method, in the form of Nonequivalent Control Group Design. The population in this study were all students of class V of SDN 24 Singkawang in the 2023/2024 academic year, totaling 46 students, namely 23 students in class VA and 23 students in class VB. The sample was taken using a probability sampling technique with a simple random sampling type. The data collection technique used a test technique in the form of a learning outcome question sheet in the form of a description (essay). The data analysis technique used a two-sample t-test and an effect size test. The results of the analysis showed that the data was normally distributed. The results of the study, 1) showed that the results of tcount> ttable, namely 3.473> 2.074, which means that there is a difference in the results of learning Indonesian in the cognitive domain of acrostic material in the RADEC learning model compared to the conventional method in class V SDN 24 Singkawang. 2) The RADEC learning model has a high influence on students' Indonesian learning outcomes in the cognitive domain of acrostic poetry material at SDN 24 Singkawang in the experimental class that received the RADEC learning model treatment with the results of the effect size test of 1.2 high criteria. So it can be concluded that there is an influence of the RADEC model on the learning outcomes of the cognitive domain of Indonesian students in class V SDN 24 Singkawang. Keywords: Influence of the RADEC learning model, learning outcomes in the cognitive domain